UK smart grid development: an expert assessment of the benefits, pitfalls and functions - Xenias, Dimitrios; Axon, Colin J.; Whitmarsh, Lorraine; Connor, Peter M.; Balta-Ozkan, Nazmiye; Spence, Alexa (Elsevier, 2015)
Making electricity grids smarter is a challenging, long-term, and ambitious process. It consists of many possible transitions and involves many actors relevant to existing and potential functions of the grid. We applied a two round Policy Delphi process with a range of sectoral experts who discussed important drivers, barriers, benefits, risks and expected functions of smarter grids, to inform the development of smarter grids. Our analysis of these expert views indicates broad consensus of the necessity for smarter grids, particularly for economic and environmental reasons; yet stakeholders also associated a range of risks and barriers such as lack of investment, disengaged consumers, complexity and data privacy with measures to make the grid smarter. Different methods for implementing smarter grid functions were considered, all thought to be more likely in urban settings. Implications for policy and future research are considered.
Keywords: Smart grid; Policy Delphi; Electricity market regulation; Active network management; Demand side response; Return on investment